Çelik karkas bir yapıda çelik ve kompozit çözümlerin ekonomik karşılaştırılması - Saydar, İrfan (Fen Bilimleri Enstitüsü, 1996)
Yüksek lisans tezi olarak hazırlanan bu çalışmada, altı katlı, diyagonalli çelik çelik karkas bir yapının, plastik hesap esasları ile elde edilen çelik ve kompozit çözümlerin karşılaştırılması yapılmıştır. Plastik hesap, adım adım analiz metodu ile çözülmüştür, bu yöntemin gereği ardaşık çözülen elastik sonuçlara SAP 90 Structural Analysis Program kullanılarak gidilmiştir. Sistem enine doğrultuda mesafeleri 6 m olan 3 açıklıktı, boyuna doğrultuda da mesfeleri 4 m olan 9 açı ki ı ki ı rijit çerçevelerden oluşmaktadır. Yapının tüm kat yükseklikleri 3 m olarak seçilmiştir. Döşeme olarak 10 cm kalınlıklı plak alınmıştır. Kolon kesitleri 3 katta bir değiştirilmiştir. Hareketli yük 500 Kg/m2, için ayrıca bölme duvar yükü alınmamıştır. Yapının çelik sistem olarak ön boyutlandırmasında düşey yükler altında, enine ve boyuna kirişler, kinematik yöntem ile hesaplanmış, seçilen kesitler kesme kuvveti ve sehim kontrolleri yapılarak boyutlandırılmıştır. Sehim hesaplarında elastik hesap ilkeleri dikkate alınmıştır. Yapı, yatay yüklere karşı kısa ve uzun doğrultuda düzenlenen ikişer adet "K" tipi düşey kafes sistemler ile stabil hale getirilmiştir. Seçilen kafes tipi sayesinde katlarda yatay sirkülasyon rahatlatılmıştır. Her iki çözüm için kolon kesitlerinde "W kesitler (Geniş başlıklı Amerikan kesitler.), kiriş kesitlerde "I " profilleri (Standart ), Diyagonallerde ise "U" kesitler ve lama kullanılmıştır. St 37 çeliği ve BS 16 betonu kullanılmış, kompozit kolonlarda ise BS 20 alınmıştır

In this study, prepared as a M. S. thesis, the steel and composite solution of a multistorey building are compared. The System consists of 3 spanned rigide frame in width, which are 6 m, and longitudinally 9 spanned rigide frame, which are supported with 10 columns and each span is 4 m. All stories are of 3.2 meters high. For the slabs, 10 cm, thick reinforced concrete plates ara chosen. The calculations of the system for both solutions ara done according to plastic design methods.The load coefficient hâs been assumed 1.7 for vertical loads. Yield strength of the steel has been assumed 2.4t/cm2 for vertical loads. 1.7G + 1.7Q. The Load coefficient has been assumed 1.5 for horizontal loads. 1.5G +1.5Q + 1.5E. Yield strength of the steel has been assumed 2.4/1.15 t/cm2 for horizontal loads. The loads coefficient has been assumed 1.0 for the calculations of deflection. In the design of the structure as a steel system, the beams in width and longitidunal directions are calculated by mechanism and step by step methods. The shear force effecting on the beams are researched and then by considering the deflection conditions the necessary changes of the sections are done. The lateral buckling of the beams are not analysed. In the design of the structure as a composite system, the sections forces obtained from the preliminary calculations are used for the beams in width andlongitidunal. The shear force and deflection analysis of the beams ara also done. In the composite solution and steel solution the control of deflection limit is not effective. XIV The stabilty of the system is guaranteed width vertical bracing trusses which do not permit to any lateral displasements. In calculations for deflection limit, elastic design rules are considered. Since the earthquake load is more unsuitable than the wind load, it is taken as the horizontal load to be considered. The earthquake load is distributed to transverse and longitudinal vertical trusses. The vertical trusses have been placed symmetrically to obtain a better response since the earthquake force may in both directions. In order to prevent the colums from excessive horizontalloads and to avoid larger profiles, after some approximations, the number of vertical trusses have been singnificantly increased and the most suitable positions for them are found. In both solutions " W " American sections for columns, " I " standart sections for beams, " [ " sections for diagonals are used. Steel St 37 and concrete B 16 and B20 are used as construction materials. The soil is clay and the structure is in the 2. degree eartquake region. Load Analysis: Normal Storey Loads: Reinforced concrete slaps, 10 cm Smoothing + protecting layer Dynamic load Top Storey Loads: Reinforced concrete slaps, 1 0 cm : 0.250 kg/m2 xv Dynamic load 0.500 kg/m2 Top Storey Loads: Reinforced concrete slaps, 1 0 cm Smoothing + protecting layer Dynamic load Steel St 37 and concrete B 16 and B20 are used as construction materials. In the longitudinal and transverse direction, the system has been taken as consisting of separete storey frames. Longitudinal and transverse beams are solved by the methods of mechanism, later the exact dimensions are obtained by considering normal force, shear force, buckling and deflection limit. In the calculation of separete storey frames for beams in the transverse and longitudinal direction, the plastic joints are suppose the form on the beams. In consideration of above mentoned situstion: Steel Constructure, axle 1-1, all interval: MM! U q =0.036 t/m kiriş zati + 0.900 t/m Do +0.56 t/m Parapet =1.499 t/m q*=1.7xq = 2.548 t/m L=6m XVI Q*xLx-xö=2OxMpx20xM 2.548x6x-x-0=40x Mp 2 2 Mp = 5.733 tm In beams in the longitudinal direction Steel constructure, secondary beam, first interval: q = (0.900 t/m2 x 2m)+(0.036 V =1.836 t/m q*=1.7xq =3.12 t/m L=6m Wdis = Wic q*xLx-x8=20xMpx20xMp 1 3.12x6x-x30=40xM/> Mp = 7.02 tm Section: I 240: Mp = 2 x Sx x oyd = 2 x 206 x 2.4 = 9.79 fm ) 9.36 tm The Fallowing Results Have Been Obtained From The Calculation of Steel Total Weight : 183,190 Kg The Total Area Of The Building : 6 x 1 8 x 36 = 3888 m2 The Weight Per 1m2 : 47.1 1 Kg / m2 xvii The Fallowing Results Have Been Obtained From The Calculation of Composite Total Weight : 137,130 Kg The Total Area Of The Building : 6 x 1 8 x 36 = 3888 m2 The Weight Per 1 m2 : 35,34 Kg / m2 In addition, in the composite solution, as the main objective is economical analysis, it has been concluded that the composite solution supplies an economy 25 percent when the steel and composite solutions are compared. However, realist economy approximate 13 percent. 25 percent economy with composite construction xvni
The comparison of steel multistorey building with steel and composite solutions
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 1996
Keywords: Ekonomik analiz; Karşılaştırmalı analiz; Kompozit malzemeler; Çelik malzemeler; Economic analysis; Comparative analysis; Composite materials; Steel materials